Gobernar remendando infraestructuras experimentales de datos - Gloria Baigorrotegui (Revue d'anthropologie des connaissances)
This article is about the governance of an experimental data infrastructure, linked to the installation of digital monitors in ten houses, connected to the National Monitoring Network implemented in five Chilean cities in order to collect and report data on the internal and external evolution of the environmental behaviour of these houses. First, STS literature on governance based on data infrastructure is introduced. Second, three types of workarounds are presented, common in the interaction of users and designers of experimental data platforms. The methodology includes interviews with its implementers, field visits and digital ethnography. The difficulties and workarounds of the project are highlighted and finally, its results are analyzed. Experimental narratives and ventriloquisms, as situated workarounds practices, make possible a more contingent and subversive governance. This research shows the fragile production of data and knowledge, postponing or hiding others, supported by promises to improve the intelligence, standardization, and objectivity of public policies via experimental digital data infrastructure projects.